Danish farmers' preferences for bio-based fertilisers - a choice experiment - Ole Bonnichsen; Brian H. Jacobsen; Juan Tur-Cardona (University of Copenhagen, Department of Food and Resource Economics (IFRO), 2020)
Within the transition towards a 'circular' economy, more farmers are searching for bio-based fertilisers, which are nutrient products based on animal manure. In Denmark, there are many collaborative agreements between farmers, and the need for manure processing is relatively low. Arable farmers typically receive the manure free of charge or for a relatively low cost (application or transport costs). However, Danish farmers might want to buy bio-based products from e.g. the Netherlands instead of mineral fertiliser depending on the product and the price. The purpose of this paper is to investigate how much Danish farmers are willing to pay for bio-based fertilisers and what characteristics of bio-based fertilisers are the most important for the farmers to start using them. We use the stated preference technique of a Choice Experiment, and present respondents with a choice between two bio-based fertiliser alternatives and their current mineral fertiliser, where the alternatives are characterised by selected fertiliser attributes. Data was collected from 202 Danish farmers. Results indicate that the farmers prefer a higher certainty in the N-content, low volume, organic carbon and hygienisation. The ideal bio-based product, which is like mineral fertiliser, but also includes organic material, typically can be sold at up to 50% of the mineral fertiliser price. The analysis also shows that some farmers are unlikely to accept bio-based fertilisers unless the product has the same properties as mineral fertilisers.
Keywords: Q15; Q16; Q56; D61; 330; Bio-based; manure; fertiliser attributes; willingness-to-pay; choice experiment